Manifestasi dan transmisi okular pada coronavirus disease 2019 (COVID-19): klinis dan pencegahan - Nyoman Brahmani Pitanatri; Ni Made Indah Kencanawati (Intisari Sains Medis, 2021)
Background: Coronavirus disease 2019 (COVID-19) pandemic is an infectious disease caused by a novel Coronavirus called Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). Respiratory tract is the main route for this virus transmission through droplets, with common symptoms as fever, cough and dyspnea. Beside the manifestation on the respiratory track, patient with COVID-19 can also have ocular complaints.Methods: In writing this article, the literature review method was used and sources consist of relevant journals obtained through online search engines.Results: Conjunctivitis and keratoconjunctivitis was the most ocular manifestation reported on patients. The eye can be one of the entry routes for the virus because of the connection between the upper respiratory tract and the ocular surface mucosa through the nasolacrimal duct.Conclusion: The ocular manifestation in COVID-19 patients must not be ignored. The eye can be port of entry of the virus. Therefore, it is important to know the ocular manifestation and prevent the transmission of COVID-19.  Latar belakang: Pandemi coronavirus disease 2019 (COVID-19) merupakan suatu penyakit infeksius yang disebabkan oleh novel coronavirus yang disebut sebagai Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). Saluran pernapasan merupakan jalur utama penyebaran virus ini, yaitu melalui droplet, dengan gejala umum berupa demam, batuk disertai dispnea. Selain bermanifestasi pada saluran pernapasan, COVID-19 juga dapat bermanifestasi pada okular.Metode: Dalam penulisan artikel ini digunakan metode tinjauan pustaka dengan bersumber pada artikel relevan yang didapatkan melalui pencarian secara daring. Hasil: Konjungtivitis dan keratokonjungtivitis merupakan beberapa manifestasi okular yang paling sering dilaporkan pada pasien dengan COVID-19. Mata dapat menjadi salah satu jalur masuk virus oleh karena adanya hubungan saluran pernapasan atas dan mukosa permukaan okuli melalui duktus nasolakrimalis.Simpulan: Manifestasi okular pada COVID-19 tidak dapat diabaikan. Mata dapat menjadi salah satu port de entry virus. Oleh sebab itu, mengenali gejala pada okular serta pencegahan trasnsmisi okular virus COVID-19 menjadi sangatlah penting.